The Effect of the Implementation of BNI SONIC (Self Service Opening Account) on Improving the Quality of Customer Service at BNI in Bali - Jaabir Jaabir; I Wayan Bagia; Putu Indah Rahmawati (International Journal of Social Science and Business, 2022)
This study was aimed to determine the level of customer satisfaction with opening an account without using a BNI SONIC machine and using BNI SONIC, as well as the effect of implementing BNI SONIC on improving service quality at BNI in Bali. This quantitative research used a questionnaire method filled in via Google Form. The data analysis technique used the Independent Sample T-Test. The results showed: (1) The level of quality of BNI customer service in opening an account by BNI Manual showed that the category of quality for customer service was “Very Low” before the implementation of BNI SONIC. (2) The level of customer service quality after the implementation of BNI SONIC, showed that results in the "Very High" quality category. (3) Based on the results of Independent Sample T-Test, there is a significant difference between the average results of the service quality of BNI Manual and BNI SONIC.